2018
DOI: 10.1007/s10040-018-1768-4
|View full text |Cite
|
Sign up to set email alerts
|

Long-term groundwater storage changes and land subsidence development in the North China Plain (1971–2015)

Abstract: The North China Plain (NCP) has been suffering from groundwater storage (GWS) depletion and land subsidence for a long period. This paper collects data on GWS changes and land subsidence from in situ groundwater-level measurements, literature, and satellite observations to provide an overview of the evolution of the aquifer system during 1971-2015 with a focus on the sub-regional variations. It is found that the GWS showed a prolonged declining rate of −17.8 ± 0.1 mm/yr during 1971-2015, with a negative correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
88
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(94 citation statements)
references
References 27 publications
6
88
0
Order By: Relevance
“…The simulated groundwater depletion estimates by Scanlon et al (2012a) are mostly consistent with available GRACE-derived groundwater depletion estimates (Famiglietti et al 2011, Scanlon et al 2012b. For the NCP, the groundwater depletion estimates produced with groundwater models (Cao et al 2013) substantially differ from those obtained using GRACE (Feng et al 2013, Huang et al 2015, Gong et al 2018. Huang et al (2015) indicated that the NCP aquifer system is highly complex, where shallow groundwater declines faster than deep groundwater, but shallow groundwater storage recovers quickly.…”
Section: Volume-based Methodssupporting
confidence: 58%
“…The simulated groundwater depletion estimates by Scanlon et al (2012a) are mostly consistent with available GRACE-derived groundwater depletion estimates (Famiglietti et al 2011, Scanlon et al 2012b. For the NCP, the groundwater depletion estimates produced with groundwater models (Cao et al 2013) substantially differ from those obtained using GRACE (Feng et al 2013, Huang et al 2015, Gong et al 2018. Huang et al (2015) indicated that the NCP aquifer system is highly complex, where shallow groundwater declines faster than deep groundwater, but shallow groundwater storage recovers quickly.…”
Section: Volume-based Methodssupporting
confidence: 58%
“…The variation in effective groundwater depth exhibited coupling and hysteresis with precipitation. In the area with extensive groundwater exploitation in the North China Plain [64], especially in the funnel area, the influence of the change in groundwater depth on the NDVI trends correspondingly weakened [65]. Considering the comprehensive effects of climatic factors on NDVI trends, climatic factors had no significant or negative effects on NDVI, which indicates that climate change had a certain negative effect on vegetation changes [66], while human activities had a great impact.…”
Section: Impact Of Climate On Ndvi Trendsmentioning
confidence: 98%
“…Agriculture depends largely on groundwater exploitation in the HRB, which is similar to the High Plains in the USA and northwest India, and it has become the major groundwater depletion areas around the world [42]. The GWS suffers a prolonged declining trend of −17.8 ± 0.1 mm/yr during 1971-2015 in the North China Plain [43], which covers most of the region of the HRB.…”
Section: Grace Datamentioning
confidence: 99%
“…In recent years, with the launch of the GRACE satellite, the water depletion in the HRB has been a research hotspot, given its significant depletion rate and important role in China [43][44][45][46][47][48][49]. Most of the water depletion is caused by agricultural irrigation in the HRB [17,44,50].…”
Section: Grace Datamentioning
confidence: 99%